1986
DOI: 10.1017/s0022172400063609
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of plasmids conferring resistance to gentamicin and apramycin in strains ofSalmonella typhimuriumphage type 204c isolated in Britain

Abstract: SUMMARYIn Salmonella typhimurium phage type 204c isolated in Britain, gentamicin resistance is specified by plasmids of the I1 compatibility group which also confer resistance to apramycin. These plasmids have been subdivided into three types within the I1 group on the basis of their antibiotic resistance specificity, their ability to produce colicin lb and their restriction enzyme digest fragmentation patterns. All three have been identified in strains from cattle, but as yet only two types have been found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
149
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 226 publications
(155 citation statements)
references
References 6 publications
4
149
0
2
Order By: Relevance
“…Additional strains of PT15 are also listed in Table 1 [8] and visualized after electrophoresis at 150 V for 2 5 h on vertical 0-7 % (w/v) Tris-borate agarose gels (Sigma, Type II, Mledium EFO). Plasmids were sized in relation to plasmids of known molecular weights carried in strains 39R861 [12] and V517 [13]. Restriction Factors governing the choice of oligosequence were: (i) about 20-30 base pairs (bp) in length; (ii) GC-rich ends, especially 3'; (iii) no hairpins or internal repeats.…”
Section: Bacteriamentioning
confidence: 99%
“…Additional strains of PT15 are also listed in Table 1 [8] and visualized after electrophoresis at 150 V for 2 5 h on vertical 0-7 % (w/v) Tris-borate agarose gels (Sigma, Type II, Mledium EFO). Plasmids were sized in relation to plasmids of known molecular weights carried in strains 39R861 [12] and V517 [13]. Restriction Factors governing the choice of oligosequence were: (i) about 20-30 base pairs (bp) in length; (ii) GC-rich ends, especially 3'; (iii) no hairpins or internal repeats.…”
Section: Bacteriamentioning
confidence: 99%
“…Apramycin-resistant E. coli and K. pneunioniae isolated from humans in the UK have also been reported [7]. An increasing prevalence of resistance to gentamicin has been found in S. typhirnuriun2 phage type 204c in humnans [8] and it has been suggested that use of apramycin in animals has selected for resistant salmonella isolates which then infect man [6].…”
Section: In'trodu( Ti()nmentioning
confidence: 99%
“…DNA was separated by electrophoresis in 0 7 % agarose gels and molecular weights of plasmnids were determined by cotmparison with four reference plasmids carried in E. coli strain 39R861 [6].…”
Section: Conjuiyationsmentioning
confidence: 99%
“…Samples were analysed by electrophoresis at 100 V for 2-2-5 h on 0-6 % horizontal agarose gels (w/v, Sigma, Type II medium EEO), using a model H5 horizontal gel apparatus (Gibco/BRL), and were sized in relation to plasmids carried in the Escherichia coli strains 39R861 [11] and V517 [12], as previously described [7].…”
Section: Bacterial Strainsmentioning
confidence: 99%